PENGARUH KOMPETENSI, MOTIVASI KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI INSPEKTORAT PROVINSI SULAWESI TENGGARA - Namirah, Danti; Yusuf, Abdul Razak; Taufik, Muhammad; Montundu, Yusuf (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2021)
This study aims: (1) to determine the effect of competence, work motivation and career development on employee performance at the Inspectorate of Southeast Sulawesi Province; (2) To determine the effect of competence on the performance of the Inspectorate of Southeast Sulawesi Province employees; (3) To determine the effect of work motivation on the performance of the Inspectorate of Southeast Sulawesi Province employees; (4) To determine the effect of career development on the performance of the Inspectorate of Southeast Sulawesi Province employees. The sample in this study were 52 employees who worked at the Inspectorate of Southeast Sulawesi Province. The analysis used is quantitative analysis using Multiple Linear Regression Analysis.Â The results showed that; (1) Competence, work motivation, and career development have a significant effect on the performance of the Inspectorate of Southeast Sulawesi Province employees; (2) Competence has a significant effect on the performance of the Inspectorate of Southeast Sulawesi Province employees; (3) Work motivation has a significant effect on the performance of the Inspectorate of Southeast Sulawesi Province employees; (4) Career development has a significant effect on the performance of the Inspectorate of Southeast Sulawesi Province employees.